SILENT UTERINE RUPTURE OF SCARRED UTERUS -AN UNUSUAL PRESENTATION AS AMNIOCELE - Wali, Aisha Syed; Naru, Tahira Yasmeen (Journal of Ayub Medical College Abbottabad, 2013)
Obstetricians should be aware of the possibility of silent rupture of scarred uterus. Ultrasound has an important role in the diagnosis of silent uterine rupture. A case of silent uterine rupture with foetal demise, that remained undiagnosed for many weeks, is described. Keywords: Silent uterine rupture, scar dehiscence, scarred uterus